On frames for Krein spaces - Giribet, J. I. (2012)
A definition of frames for Krein spaces is proposed, which extends the notion of ℐ-orthonormal bases of Krein spaces. A ℐ-frame for a Krein space (ℋ,[,]) is in particular a frame for ℋ in the Hilbert space sense. But it is also compatible with the indefinite inner product [ , ], meaning that it determines a pair of maximal uniformly ℐ-definite subspaces, an analogue to the maximal dual pair associated to a ℐ-orthonormal basis. Also, each ℐ-frame induces an indefinite reconstruction formula for the vectors in ℋ, which resembles the one given by a ℐ-orthonormal basis.